Comparative performance of green rusts generated in Fe0–electrocoagulation for Cd2+ removal from high salinity wastewater: Mechanisms and optimization. (1st May 2019) - Xu, Longqian; Wu, Deli; Liu, Wei; Xu, Xiaojun; Cao, Guangzhu
Abstract: The treatment of wastewater containing high concentration of inorganic salts has always been one of the focuses of environmental researchers. In this work, the effect of Cl − and SO4 2− on the removal of Cd 2+ from wastewater using Fe 0 -electrocoagulation (Fe 0 -EC) were investigated by evaluating the transformation of Fe mineral. The experimental results indicated that the removal of Cd 2+ from wastewater was depended on the property of Fe minerals. The generation of sulfate green rust (GRSO4 ) produced in the presence of SO4 2− showed stronger adsorption than the chloride green rust (GRCl) for Cd 2+, and GRSO4 was obtained even in the mixture Cl − and SO4 2− solutions, because Fe(II)–Fe(III) GRs (layered double hydroxides, LDHs) showed stronger affinity for divalent SO4 2− than monovalent Cl − . High concentration of inorganic anions in wastewater resulted in the negative charged Fe flocs. High concentration of Cl − promoted the oxidation of Fe(II) to Fe(III) by chlorine–containing oxidants, and increased the proportion of Fe(III)/Fe(II) in Fe flocs, secondary Fe mineral magnetite (Fe3 O4 ) was formed because of the increase of pH. Therefore, the presence of GRSO4 intermediate increased the Cd 2+ removal by adsorption (coagulation and coprecipitation), and then the generated GRSO4 were gradually transformed into lepidocrocite (γ–FeOOH) by oxygen from air. Finally, the parameter optimization were conducted by adjusting the ratio of Cl − and SO4 2− ( R C:S ), current density ( j ), initial pH (pH i ), initial Cd 2+ concentration ( C 0 ), and temperature ( T 0 ). The removal efficiency of Cd 2+ reached 99.5% after 10 min Fe 0 -EC under the optimal parameters: R C:S = 25:50 mmoL/mmol, j = 6 mA/cm 2, pH i = 7–9, and T 0 = 40 °C. Highlights: The effect of Cl − and SO4 2− ratios on the removal of Cd 2+ was studied. The generation and transformation of Fe mineral was investigated. The generation of sulfate green rust favored the adsorption of Cd 2+ . The optimal EC parameters for the Cd 2+ removal were obtained.